Improving geothermal doublet efficiency in multiple sandstone horizons in Hannover/Germany - Jonas Suilmann; Torsten Tischner; Thomas Graf (Grundwasser, 2025)
In Hannover, Germany, a deep borehole was drilled to explore the use of geothermal energy for the heat supply of office buildings. The targets are multiple subdivided sandstone horizons of the Wealden formation (Lower Cretaceous) at a depth of 1200–1300 m and a temperature of around 70 °C. The technical feasibility of the doublet operation is assessed by numerically investigating the effects of well spacing, injection/production rate and injection temperature using a 3D model. In particular, the production temperature drop is investigated to optimize well spacing and doublet lifetime. The effect of uncertain sandstone permeability and surrounding rock thermal conductivity on doublet lifetime is also investigated. The results indicate that a doublet well spacing of 500 m can sustain heat production with a thermal power output of 0.5 to 2 MW over a lifetime of at least 30 years, demonstrating the general feasibility of geothermal heat production from multiple sandstone horizons.

Pressure-dependent Production Efficiency of an Enhanced Geothermal System (EGS): Stimulation Results and Implications for Hydraulic Fracture Treatments - Günter Zimmermann; Torsten Tischner; Björn Legarth; Ernst Huenges (Pure and Applied Geophysics, 2009)